Cystic Hygroma in Children: Comparison Between Sclerosing Treatment With Bleomycin Vs Surgical Resection (Medical Forum Monthly, 2020)
Objective: To compare the outcome of sclerotherapy with bleomycin versus surgical resection in children in cystic hygroma.Study Design: Comparative/ObservationalPlace and Duration: This study was conducted at the Department of Paediatric Surgery, Bolan Medical Complex Hospital Quetta from 1st January 2019 to 30th June 2019.Materials and Methods: Forty patients of both genders with ages 1 month to 15 years presented with cystic hygroma were included in this study. Patients detailed demographic were recorded after written consent from parents/guardians. Patients were divided in to two groups’ i.e. Group A consist of 20 patients and received sclerotherapy with intra-lesional bleomycin and Group B consist of 20 patients received surgical excision. Outcomes were analyzed at post-procedure 3 and 6 months post-procedure and compare the findings between both groups.Results: There were significant difference observed between both groups regarding age, gender and site of lymphangioma p-value >0.05. In Group A 15 (75%) patients showed excellent results, 3 (15%) patients showed good results and 2 (10%) showed poor results. In Group B 9 pts (65%) showed excellent results, 5 (20%) showed good results and 6(15%) showed poor results. At final follow-up there were 2 patients with recurrence in Group A while in Group B 5 (10%) patients had recurrence,Conclusion: Sclerosing treatment with bleomycin is safe and effective treatment modality with no recurrence as compared to surgical resection.